K-MODAL BL-ALGEBRAS - Yousefi Kia, O; Eslami, E; Borumand Saeid, Arsham (Kuwait Journal of Science, 2016)
This article will introduce K-modal BL-algebra and investigate some properties ofthis new algebra. Consequently, K-modal filters and □-tautology filters as filters ofK-modal BL-algebras will be dealt with. We will prove that the class of all K-modalBL-algebras is a variety of algebra. Our final goal in this paper is to prove that aK-modal BL-algebra is a sub-algebra of direct product of a system of linearly orderedK-modal BL-algebras under special conditions.